Student Interest and Motivation in Physical Education, Sports, and Health after COVID-19 - Khairul Khairul; Andika Triansyah; Novi Yanti (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. The COVID-19 pandemic brought about a significant transformation in learning methods, especially in Indonesia. For almost two years, physical education, sports, and health classes were conducted online from home, and now there is a shift back to in-person learning, both in classrooms and in practical settings. Our research aims to evaluate the level of students' motivation and enthusiasm towards participating in physical education, sports, and health classes after the pandemic. This study will delve into the technical details of the changes in the learning methods and assess the effectiveness of these changes. Material and methods. The study employed a descriptive quantitative research design using a survey method. All 127 VIII-grade students at SMP Negeri 2 Mempawah Hilir were selected as the research sample using a saturated sample technique. The data collection technique used indirect communication through a closed questionnaire that employed the Likert Scale to measure attitudes. Students answered several statements in the questionnaire directly. Results. Based on the gathered data, the research results indicate that at SMP Negeri 2 Mempawah Hilir, 78% of students, which amounts to 99 students out of 127 students, have a high interest in learning physical education sports and health after the COVID-19 pandemic. Similarly, 73% of students, which accounts for 93 students out of 127 students, have a high motivation to learn physical education sports, and health after the COVID-19 pandemic. Conclusions. Based on the results obtained, it can be inferred that the students have shown a significant level of enthusiasm towards physical education, sports, and health even after the COVID-19 pandemic. The evidence suggests that physical education is highly valued by the students for their overall wellness and fitness.